Predictive factors of outcome in patients with Tetralogy of Fallot (TOF) after pulmonary valve replacement: preliminary data of our Centre experience (2010-2020). (4th February 2022) - Cavaliere, A; Vivian, LM; Puricelli, F; Reffo, E; Di Salvo, G
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: TOF patients undergo multiple surgical procedures during their life. The improvement in surgical techniques and patient's clinical management led to longer life expectancy, creating an adult TOF population that experiences specific adverse events, such as atrial/ventricular arrythmias, heart failure and sudden cardiac death. In selected patients, pulmonary valve replacement (PVR) is mandatory to reduce right ventricular (RV) volume; therefore, careful patients' selection but also correct timing of PVR are crucial. Purpose: Current guidelines are based on pre-PVR threshold values of indexed RV end-diastolic volume (RVEDVi) calculated with cardiac magnetic resonance (CMR), to achieve normalization of RV size after valve implantation, but recent studies demonstrated that post-PVR RV dilatation is not so tightly connected with adverse clinical outcomes. Therefore, our aim is to identify new possible predictive factors of post-PVR outcome to provide tailored PVR on the correct cohort of patients, at the correct time. Methods: The inclusion criteria of this retrospective and partially prospective cohort study were: i) repaired TOF; ii) available CMR data pre- and post-PVR; iii) PVR performed between 2010 and 2020; iv) clinical and ECG available pre- and post-PVR; v) complete echocardiographic examination pre- and post-PVR. Multivariate analysis was applied. Primary outcomes were considered death, resuscitated death, atrial/ventricular arrhythmias. NYHA class was considered to evaluate patients' clinical status. CMR Late Gadolinium Enhancement (LGE) score was calculated pre- and post-PVR. Results: 22 patients were selected (12 males, median age ± SD 28, 25 ± 11, 2 years). After PVR, the only primary outcome observed was sustained ventricular tachycardia in 4 patients. Multivariate analysis showed that patients with later PVR, lower Fractional Area Change (FAC) at pre-PVR echocardiogram and higher LGE score post-PVR (LGE > 3) showed higher post-PVR RVEDVi. On the contrary, patients with class I NYHA post-PVR showed lower RVEDVi. Conclusion: Our study demonstrates that lower age at PVR and careful patient's selection, guided by echocardiographic and CMR findings, lead to greater benefit in terms of good volumetric recovery of the RV and better performance status post-PVR (NYHA class I) in TOF patients after PVR.